Incidence of Dentinal Crack Formation Using ProTaper Universal and WaveOne Systems in Straight and Curved Root Canals - Akhlaghi, Nahid Mohammadzade; Delvarani, Abbas; Norouzi, Vanousheh; Mohebbi, Pooneh; Meraji, Naghmeh (Iranian Endodontic Journal, 2018)
Introduction: This study aimed to compare dentinal micro crack formation following root canal instrumentation with ProTaper Universal (PTU) and WaveOne (WO) rotary systems in straight and curved root canals. Methods and Materials: One hundred mesiobuccal (MB) straight and curved canals of mandibular molars meeting inclusion criteria were divided into two control (n=10) and four experimental groups (n=20). After mounting the teeth and simulating the periodontal ligament, all the MB canals were coronally flared using Gates-Glidden drills #3 and 2 respectively. Then, in the experimental groups, the canals were instrumented with either PTU files (Sx, S1, S2, F1, F2), or Primary WO (25/0.08). Afterwards, roots were horizontally sectioned at 2, 4, and 6 mm from the apices, and evaluated under a microscope under 20× magnification. Data were analyzed with the Chi-Square and Kruskal-Wallis tests. The significance level was set at 0.05. Results: The control groups showed no cracks. There was no significant difference between the two systems in the straight root canals (P>0.05). But in the curved root canals, PTU produced significantly more cracks (P<0.05) with the complete crack type which was dominant (P=0.013) compared to WO. Conclusions: This in vitro study showed that in curved root canals, instrumentation with reciprocal WO system may be safer than full rotational PTU instruments regarding crack formation. Keywords: Crack; Dentin; Instrumentation; Reciprocating; Root Canal Preparation